Comparison between conventional and molecular methods to detect parasitic infections in patients with neurological symptoms from cerebrospinal fluid / Vanitah Supramaniam - Vanitah, Supramaniam (2017)
Neurological problems in patients require rapid diagnosis for accurate detection and timely treatment for better management and cure. Rarely, clinicians correlate the problem to presence of parasitic infections. Active metabolite, cerebrospinal fluids (CSF) was exploited to assess if parasitic infections in patients with neurological symptoms can be detected. Total of 238 cerebrospinal fluids specimens was investigated using conventional staining and polymerase chain reactions (PCR) using primers targeted for Acanthamoeba spp, Entamoeba spp, Blastocystis spp and Toxoplasma gondii spp infections. Eight out of 238 specimens, show some parasite-like microorganism from conventional staining methods. However, polymerase chain reaction subjected to identified parasite-like microorganism shows negative results. Conversely, eleven samples were identified to have Toxoplasma gondii infections from nested polymerase chain amplification. Data collected from medical record office, University of Malaya Medical Center (UMMC) indicated, all these 11 specimens show elevated leucocytes and protein level in cerebrospinal fluid analysis and decrease in glucose in few cases. Although with various medical history, these patients can be grouped under immuno-compromised category and shows some common neurological symptoms, such as seizure, fever, vomiting, generalized body weakness and slurred speech. Cerebrospinal fluids can be used for the detection of parasite Toxoplasma using nested PCR. Patients with neurological symptoms especially, immuno-compromised patients negative for microbiological and other routine preliminary diagnosis could be positive for opportunistic parasite infections such as Toxoplasma gondii. Thus, detection of Toxoplasma gondii infection by molecular method should be considered and implemented at preliminary stage to specimens with unknown etiologic agent with prolonged symptoms.